Nanoglasses: A New Kind of Noncrystalline Material and the Way to an Age of New Technologies?. Issue 16 (12th January 2016) - Gleiter, Herbert
Abstract : Today's technologies are primarily based on crystalline materials (metals, semiconductors, etc.), as their properties can be controlled by varying their chemical and/or defect microstructures. This is not possible in today's glasses. The new features of nanoglasses—consisting of nanometer‐sized glassy regions connected by interfaces—are that their properties may be controlled by varying their chemical and/or defect microstructures, and that their interfaces have a new kind of non‐crystalline structure. By utilizing these new features, an age of new technologies based on non‐crystalline materials (a "glass age") may be initiated. Abstract : Today's technologies utilize primarily crystalline materials, as their properties can be controlled by varying their chemical and/or defect microstructures. This is not possible in today's glasses, but it could be possible in nanoglasses. Their two new features are that their properties may be controlled by varying their chemical and/or defect microstructures, and their interfaces have a new kind of noncrystalline structure. By utilizing these features, an age of new technologies may be initiated.